2022
DOI: 10.1021/acsomega.2c02832
|View full text |Cite
|
Sign up to set email alerts
|

Click-Chemistry-Mediated Synthesis of Silver Nanoparticle-Supported Polymer-Wrapped Carbon Nanotubes: Glucose Sensor and Antibacterial Material

Abstract: We report a novel approach for the synthesis of silver nanoparticles (NPs) stabilized on polymer-wrapped carbon nanotubes (Ag@polymer/CNTs) for the non-enzymatic glucose sensing and antibacterial activity applications. Poly­(styrene-alt-maleic anhydride) (PSM) was functionalized with amino furan to obtain furan-modified poly­(styrene-alt-maleic anhydride) (PSMF), which was later grafted onto the surface of CNTs by Diels–Alder “click” reaction to afford a polymer/CNTs hybrid material. The photo-deposition techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Moreover, pH-sensitive polysaccharide-gold nanorod conjugate ( Hou et al, 2019 ) and polymer nanomicelle platform ( Figure 1H ) ( Liao et al, 2021 ) were reported to treat cancers via hydrazone click reaction and CuAAC, respectively. In addition, silver nanoparticle-supported polymer-wrapped carbon nanotubes (CNT) ( Cao et al, 2022 ) for non-enzymatic glucose sensing and antimicrobial applications ( Figure 1I ), COF-based nanoreactors for click-activated pro-drug delivery and precise anti-vascular therapy ( Wang et al, 2022 ) had been synthesized via IEDDA, these click chemistry-based targeting strategies may find widespread application in drug delivery in the future.…”
Section: Click Chemistrymentioning
confidence: 99%
“…Moreover, pH-sensitive polysaccharide-gold nanorod conjugate ( Hou et al, 2019 ) and polymer nanomicelle platform ( Figure 1H ) ( Liao et al, 2021 ) were reported to treat cancers via hydrazone click reaction and CuAAC, respectively. In addition, silver nanoparticle-supported polymer-wrapped carbon nanotubes (CNT) ( Cao et al, 2022 ) for non-enzymatic glucose sensing and antimicrobial applications ( Figure 1I ), COF-based nanoreactors for click-activated pro-drug delivery and precise anti-vascular therapy ( Wang et al, 2022 ) had been synthesized via IEDDA, these click chemistry-based targeting strategies may find widespread application in drug delivery in the future.…”
Section: Click Chemistrymentioning
confidence: 99%
“…Metal nanoparticles often play a major role, giving nanocomposites distinctive properties. In particular, the nature and composition of these nanoparticles largely dictate the catalytic [34,35], magnetic [36,37], photocatalytic [38], electrochemical [39][40][41], sensory [42], and antibacterial [43] characteristics of nanocomposite materials.…”
Section: Introductionmentioning
confidence: 99%